Religion in sixteenth-century Mexico: a guide to Aztec and Catholic beliefs and practices - Claassen, Cheryl (Cambridge University Press, 2022)
"Religion in 16th Century Mexico explores the development of religion as transferred from Spain to Tenochtitlan. The religious world of both Aztecs and Spanish Catholics at time of encounter was organized through large and small scale community, family, and personal devotions. Devotion expressed through cults was the single most salient aspect in the transfer of Catholicism to New World people. This book highlights the role that ideas such as afterlife, apocalypticism, iconoclasm, Marianism, resistance, and saints played in the emergence of Mexican Catholicism in the 16th century. The larger Atlantic world context, as seen in the regions of Iberia, Anahuac, and "New Spain", or central Mexico from Zacatecas to Oaxaca, is explored in detail. Beginning with an extensive historical essay to contextualize the precontact period, the bulk of this volume contains 118 separate keywords each with three comparative essays examining Aztec and Catholic religious practices before and after contact"--